Indoloindole-based small molecule bulk heterojunction small molecule solar cells. (February 2019) - Sung, Min Jae; An, Na Gyeong; Wang, Canjie; Kim, Yun-Hi; Kim, Jin Young; Kwon, Soon-Ki
Abstract: An acceptor-donor-acceptor (A-D-A) conjugated small molecule, DHII-EH-TR, was designed, synthesized, and its solar cell performance studied. The DHII-EH-TR molecule with its extended fused aromatic core had a narrow bandgap and displayed red-shifted absorption. To investigate its photovoltaic properties and device application, small molecule-based organic photovoltaics (SMOPVs) were fabricated having the conventional structure of ITO/PEDOT:PSS/DHII-EH-TR:PC70 BM/ZnO NPs/Al (PEDOT:PSS, poly (3, 4-ethylenedioxythiophene):polystyrene sulfonic acid; ZnO NPs, ZnO nanoparticles). Solar cells made with a blend of 1, 8-diiodooctane with ZnO NPs generated the highest performance with a power conversion efficiency (PCE) of 3.60%. Charge dynamics and transport, microscopic thin film analysis, and morphology were studied to explain the performance of SMOPVs made with DHII-EH-TR. Highlights: An acceptor-donor-acceptor (A-D-A) conjugated small molecule. Indolo [3, 2-b]indole as core unit and 3-ethylrhodanines as the acceptor groups. The photovoltaic properties of DHII-EH-TR were investigated. Solar cell devices with 1, 8-diiodooctane and ZnO nanoparticles generated PCE of 3.60%.